Legal Protection Effort Against Consumers Regarding Electronic Transaction Violations During The Covid-19 Pandemic - Bambang Eko Turisno; Early Romansa Budi (Green Publisher Indonesia, 2022)
The development of technology has made all forms of life easy for humans. One of the technological advances is the existence of internet technology. The presence of e-commerce provides convenience that is very, very useful for consumers. In connection with the economic problems that resulted in the decline in the economy during the COVID-19 pandemic, in this case, it gave rise to new crimes and the level of criminalization in society was increasing. Fraud cases in electronic transactions are one of the crimes commonly committed on social media or e-commerce. The purpose of this paper is to find out the legal protection for consumers regarding violations of electronic transactions during the covid-19 pandemic. Legal protection for consumers due to violations including fraud through electronic transactions during the covid-19 pandemic is regulated through the provisions in the Indonesian Criminal Code, which is contained in Article 378 concerning Fraud and its provisions in the ITE Law as these regulations have regulated relating to an electronic transaction that is in Indonesia, this clause is part of positive law in Indonesia that can be used as an effort to protect the law